Fintech, pandemic, and the financial system : challenges and opportunities - Kim, Suk-Joong (International finance review, 2023)
Financial institutions are facing unprecedented challenges brought on by the coronavirus Pandemic, less than a decade after recovering from the Global Financial Crisis and the Eurozone debt crisis. The causes of these challenges differ greatly from the previous crises that financial institutions, to a large extent, had contributed to. The current challenges were exogenous and unpredictable, and their consequences will reshape the financial system architecture around the world. Fintech, once dismissed as no more than a novel approach to servicing the segment of the population often overlooked by established financial intermediaries, is now challenging the traditional models of commercial and investment banking. The inevitable future introduction of digital currencies that could replace national currencies in many business transactions has the potential to fundamentally change the business models of financial institutions and how the financial system functions. Volume 22, Fintech, Pandemic, and the Financial System, examines systemic challenges faced by a wide range of financial market participants and the continued disruptions introduced by financial innovations (Fintech). International Finance Review publishes theme-oriented volumes on various issues in international finance, such as international business finance, international investment and capital markets, global risk management, international corporate governance and institution, currency markets, emerging market finance, international economic integration, and related issues.